Donor Insemination: International Perspectives - Elston, Mary Ann (Journal of medical ethics, 2000)
Donor insemination (DI) is a neglected topic among social scientists. According to its editors, both established sociological experts in the study of assisted conception, this collection is the first of its kind. The reasons for this social scientific neglect must include DI's relatively “low-tech” character as a procedure (in comparison with so-called “new reproductive technologies” and the secrecy which has, historically, surrounded its use. As contributors to this book document, in the last decade the move to cryopreservation of semen in sperm banks, for example to permit screening for HIV/AIDS antibodies, has increased the technical complexity a little. And, following legislation or official guidelines, some information about semen providers and recipients and resulting offspring is now collected centrally in some countries, including the UK. But, at present, we still know very little about who has resorted to DI, …